Ketrampilan dan Kepemimpinan Partisipatif Kiai Majlis Dzikr Talim Sabilunnajah Kabupaten Blitar dalam Meningkatkan Ibadah Jamaah - Kusumawati, Dina (Fakultas Dakwah UIN KHAS Jember, 2024)
The presence of moral crises and advancements in education and technology in this era tends to elevate human intellectual levels and provide easy access to knowledge, especially in the realm of religion. However, the impact of this digitalization often leads many to overlook the importance of education and their social interactions. Most individuals lean towards living in isolation, rarely engaging with neighbors or friends. Dzikir gatherings emerge as a solution to enhance social life among people. The research aims to understand the leadership skills of Kiai and to identify participatory leadership among them, utilizing a qualitative descriptive approach. The findings reveal that leadership skills in the Dzikir Ta'lim Sabilunnajah include: 1) Technical skills, where Kiai demonstrate proficiency in understanding and elucidating Quranic verses; 2) Kiai exhibit strong interpersonal skills; and 3) Kiai possess the ability to grasp the bigger picture of various issues and relate them to different behaviors within the organizational context. Participatory leadership entails: 1) Setting a good personal example; 2) Motivating congregants; 3) Conducting development and training programs; 4) Creating a supportive environment; and 5) Democratic-charismatic leadership plays a crucial role in the development of the Majlis